Can Universities be a Gleam of Hope During COVID-19? Entrepreneurial Intentions Approach for Academia in Pakistan - Li, Guohao; Pervaiz, Sabeeh; He, Qi (Frontiers in Education, 2021)
The COVID-19 epidemic has wreaked havoc on the economics of several countries. Downsizing, job shortages, and unemployment are among the significant effects. The markets are supported by the need to train and educate our youth to be job producers rather than job seekers. This study sought to investigate the role of universities in the formation of students’ attitudes toward entrepreneurship by analyzing the influence of locus of control, extracurricular activities, and curriculum on entrepreneurial intention among Pakistani university students. This study collected data from 536 students across 15 universities in Pakistan through a weblink questionnaire. SPSS and AMOS were used to test the theoretical model. Results confirmed that locus of control positively affects entrepreneurial intentions and is the strongest predictor among the other two variables. Extracurricular activities positively affect entrepreneurial intentions, and curriculum is also positively affecting entrepreneurial intentions. This study concluded that entrepreneurial education and acquaintance are essential in bringing entrepreneurial intentions among students. Locus of control is found to be the most substantial element in developing entrepreneurial intentions among students. Educational institutions can play a critical role by proactively contributing through their efficient and proficient curricula, professional and experienced teachers, and locus of control by combining curricular and co-curricular activities.